Effect of del nido cardioplegia use on kidney injury after coronary bypass operations - Kağan AS,Ahmet (2021)
SUMMARY OBJECTIVE: After cardiac surgery, acute kidney injury is observed at a rate of 5–30%, and the second most common cause of acute kidney injury in intensive care units is cardiac surgery. In this study, we aimed to investigate the effect of del Nido cardioplegia solution use on postoperative acute kidney injury development in patients who underwent coronary artery bypass grafting operation with cardiopulmonary bypass. METHODS: Consecutive patients who underwent an elective coronary artery bypass grafting operation with cardiopulmonary bypass in our clinic between March 15, 2019, and March 15, 2020, were included in the study retrospectively. The patients were divided into two groups as those who received del Nido cardioplegia solution (Group 1) and blood cardioplegia (Group 2), and factors affecting the development of renal failure were examined. RESULTS: A total of 350 consecutive patients were included in the study. There were 156 patients in the del Nido cardioplegia group and 194 patients in the blood cardioplegia group. Among the patient group, 74 (21.1%) patients developed acute kidney injury. The total acute kidney injury development rate was significantly higher in Group 2 (p=0.018). In multivariate logistic regression analysis, advanced age (OR 1.128; 95%CI 1.044–1.217; p=0.042), increased blood product use (OR 1.318; 95%CI 1.154–1.998; p=0.019), preoperative creatinine elevation (OR 2.434; 95%CI 1.655–4.639; p=0.005), and increased cardioplegia volume (OR 1.254; 95%CI 1.109–2.980; p=0.009) were independent predictors of acute kidney injury. CONCLUSION: With this study, we showed that the use of del Nido cardioplegia solution can reduce the incidence of acute kidney injury.